Women's voices and feminism in Polish cultural memory - Chowaniec, Urszula; Phillips, Ursula (Cambridge Scholars Publishing, 2012)
Every time a so-called "woman's voice" appears in the media in connection with any sphere of creative activity, it finds itself confronted by the almost formulaic expression "feminism today," instantaneously suggesting that feminism is, in fact, a matter of the past, and that if we want to return to this phenomenon, then we need to explain ourselves. Women's Voices and Feminism in Polish Cultural Memory seeks to elaborate the problem of generalization, expressed by such formulas as "feminism ...